2021
DOI: 10.1002/mar.21599
|View full text |Cite
|
Sign up to set email alerts
|

Consumer cynicism in service failures

Abstract: Despite growing corporate commitments to being customer-centric, many customers perceive firms as self-driven and caring only about their own business interests. This sentiment is projected in consumer cynicism, or negative consumer attitudes based on the disbelief in the sincerity of firms' motives and actions. We argue that consumer cynicism emerges in response to negative marketplace situations, such as service and product failures. Across four scenario-based experiments and one video-based experiment, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…For example, Helm (2004) has utilized a grounded theory approach using in-depth interviews to As seen in our bibliometric review, the advanced field of organizational cynicism gives way to the nascent area (Helm, 2004) of consumer cynicism research. We advance the core construct by proposing an integrated model of consumer cynicism based on the existing findings in the organizational (Andersson, 1996;Andersson & Bateman, 1997;Chiaburu et al, 2013;Dean Jr et al, 1998;Reichers et al, 1997;Stanley et al, 2005) and consumer (Balaji et al, 2018;Chylinski & Chu, 2010;Helm, 2004;Helm et al, 2015;Indibara & Varshney, 2020;Ketron, 2016;Odou & De Pechpeyrou, 2011;Tran et al, 2022) cynicism research.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Helm (2004) has utilized a grounded theory approach using in-depth interviews to As seen in our bibliometric review, the advanced field of organizational cynicism gives way to the nascent area (Helm, 2004) of consumer cynicism research. We advance the core construct by proposing an integrated model of consumer cynicism based on the existing findings in the organizational (Andersson, 1996;Andersson & Bateman, 1997;Chiaburu et al, 2013;Dean Jr et al, 1998;Reichers et al, 1997;Stanley et al, 2005) and consumer (Balaji et al, 2018;Chylinski & Chu, 2010;Helm, 2004;Helm et al, 2015;Indibara & Varshney, 2020;Ketron, 2016;Odou & De Pechpeyrou, 2011;Tran et al, 2022) cynicism research.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies on the concept of cynicism can be found in the literature, which examine it as a conceptual, dependent, or independent variable. For example, Durmuş (2022), Kaya et al (2022), Mills and Keil (2005), Andersson andBateman (1997), andTran et al (2022) have conducted research on cynicism. Some studies also explore the mediating role of cynicism in the relationship between different concepts, such as Fayganoğlu (2021), Yıldırım and Ceyhan (2020), Genç (2018), Çoban and Deniz (2021), Ajawarneh and Atan (2018), and Ogunfowora et al (2018).…”
Section: The Mediating Role Of Organizational Cynicism Behaviormentioning
confidence: 99%
“…Word-of-mouth communication is considered the consequent, or, in other words, the result of consumer cynicism (Tran et al, 2022). Thus, it is stated that consumers who develop a cynical attitude towards businesses and their activities tends to share this attitude with negative rhetoric.…”
Section: The Relationship Between Word Of Mouth Communication and Con...mentioning
confidence: 99%